Rolled copper foil and surface treatment process thereof

By electroplating the Zn-Ni-Mo alloy layer on the calendered copper foil and optimizing the passivation steps, the existing copper foil oxidation and discoloration at high temperatures is solved, and higher heat resistance and oxidation resistance are achieved. At the same time, it replaces the toxic hexavalent chromium oxidation process, improving safety and environmental protection.

CN119710841APending Publication Date: 2025-03-28ZHEJIANG GARDEN NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411735994.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing calendered copper foils are prone to oxidation and discoloration at high temperatures, and the use of toxic hexavalent chromium oxidation processes has problems of safety and low current efficiency.

Method used

The passivation process is adopted to electroplate the Zn-Ni-Mo alloy layer, and the passivation steps are optimized to improve the heat resistance and oxidation resistance of the copper foil by adding additives such as ammonium citrate, sorbitol, sodium dodecyl sulfate.

Benefits of technology

It significantly improves the heat resistance and oxidation resistance of the rolled copper foil, avoids oxidation and discoloration at high temperatures, and replaces the toxic hexavalent chromium oxidation process, improving safety and environmental protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of rolled copper foil preparation, in particular to rolled copper foil and a surface treatment process thereof. According to the method, the process is optimized, and toxic hexavalent chromium electroplating is replaced by optimizing the passivation step and electroplating the Zn-Ni-Mo alloy layer, so that the safety and environmental friendliness are improved, meanwhile, the heat resistance and oxidation resistance of the rolled copper foil are improved, and the requirements of industrial manufacturing are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rolled copper foil preparation, and in particular to a rolled copper foil and a surface treatment process thereof. Background Art

[0002] In recent years, the development, production and sales of thick copper foil copper clad laminates and thick copper layer printed circuit boards have become popular in the industry, prompting a rapid increase in the market demand for thick copper foil. Generally, copper foil with a thickness greater than 105µm is called thick copper foil, which is generally used in high-current substrates and requires thick copper foil to have the performance advantages of high current and high voltage resistance and fast heat dissipation. Therefore, the copper foil must have excellent heat resistance, good anti-oxidation performance, and high thermal conductivity.

[0003] The raw copper foil only has physical properties such as tensile strength and elongation. Other properties such as peel strength, high temperature oxidation resistance and side corrosion resistance can only be obtained after surface treatment. Surface treatment is to use the raw copper foil as the original foil, and through a series of treatment processes, a uniform nodule-like copper roughening layer is formed on the surface to improve the peel strength; Zn, Ni, Cr and their alloys are electro-deposited to form a dense anti-oxidation layer to meet the high temperature oxidation resistance requirements of copper clad laminates and PCB processing. In order to improve the oxidation resistance of copper foil, Cr is currently mainly used in the post-processing passivation process of copper foil. 6+ The oxidation process is used to improve the oxidation resistance of copper foil. Its main disadvantages are toxicity and low current efficiency. Summary of the invention

[0004] The present invention aims to provide a surface treatment process for rolled copper foil, which not only improves safety and environmental protection, but also improves the heat resistance and oxidation resistance of the rolled copper foil.

[0005] In order to achieve the above technical purpose, the passivation process conditions are as follows: the temperature of the plating solution is 35-45°C, the concentration of zinc oxide is 8-15g / L, the concentration of sodium hydroxide is 80-100g / L, the concentration of nickel sulfate is 5-10g / L, the concentration of sodium molybdate is 3-8g / L, the concentration of ammonium citrate is 10-20g / L, the concentration of sorbitol is 1-5g / L, the concentration of sodium dodecyl sulfate is 0.2-1g / L, the pH value is 8-12, and the current density is 1-5A / dm 2 , electroplating time 1-3min.

[0006] Preferably, the passivation process conditions are: plating solution temperature 40°C, zinc oxide concentration 15g / L, sodium hydroxide concentration 90g / L, nickel sulfate concentration 8g / L, sodium molybdate concentration 6g / L, ammonium citrate concentration 15g / L, sorbitol concentration 3g / L, sodium dodecyl sulfate concentration 0.6g / L, pH value 10, current density 3A / dm 2 , electroplating time 2min.

[0007] Preferably, 105-140 μm high-purity rolled copper foil is used, and the copper mass content is greater than 99.9%. The specific steps are as follows: annealing, electrolytic degreasing, first water washing, pickling, second water washing, first roughening, third water washing, first curing, fourth water washing, second roughening, fifth water washing, second curing, sixth water washing, passivation, seventh water washing, silane coating, and drying.

[0008] Preferably, the annealing conditions are: maintaining the temperature in an oven at 270-290°C for 1-3 minutes, and then air cooling. Annealing the rolled copper foil to a semi-hard state can change its texture orientation and recrystallize into a rotated cubic texture equiaxed crystal, thereby avoiding the occurrence of browning bright spots when used by downstream customers.

[0009] Preferably, the electrolytic degreasing conditions are: 3-4wt% or more of BASF degreasing agent, temperature 25-50°C, current density 10-20A / dm 2 , electroplating time 5-15s. The concentration of BASF degreasing agent will affect the oil content on the surface of the rolled foil. If the degreasing is not clean, it will lead to uneven electroplating, poor heat resistance and anti-oxidation performance, so it is necessary to choose a degreasing agent of appropriate concentration.

[0010] Preferably, the process conditions of the first roughening and the second roughening are: the temperature of the roughening bath is 25-50°C, Cu + Concentration 30-50g / L, H + Concentration 110-130g / L, current density 15-40A / dm 2 , electroplating time 5-10s.

[0011] Preferably, the process conditions of the first curing and the second curing are: the temperature of the curing tank is 20-30°C, Cu + Concentration 40-60g / L, H + Concentration 70-90g / L, current density 30-50A / dm 2 , electroplating time 5-15s.

[0012] Preferably, the silane coating conditions are as follows: the temperature of the silane coupling agent is 20-30° C., and 1-3 ml is taken and rolled evenly. The silane coupling agent is coated to form a uniform silane treatment layer to improve the adhesion between the copper foil and the copper clad laminate substrate.

[0013] Preferably, the pickling conditions are: pickling solution temperature 20-30°C, H + Concentration 110-130g / L, Cu + Concentration 20-40g / L, soak for 5-15s.

[0014] Preferably, the water washing conditions are: pH value of 7-7.5, chloride ion content of 0.6-1ppm, and soaking for 5-15s.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Optimize the passivation step and electroplate the Zn-Ni-Mo alloy layer to replace the toxic hexavalent chromium, which not only improves the safety and environmental protection, but also takes into account the anti-oxidation property of the electrolytic copper foil.

[0016] 2. When electroplating the Zn-Ni-Mo alloy layer, ammonium citrate, sorbitol complexed metal ions, and sodium dodecyl sulfate were added as additives to increase the cathode polarization during alloy deposition and improve the heat resistance and oxidation resistance of the rolled copper foil. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Use 105-140 μm high-purity rolled copper foil, and the copper mass content is greater than 99.9%. For the convenience of comparison, 105 μm high-purity rolled copper foil is selected in the embodiment, and the copper foil is cut into a size of 100*120 mm.

[0019] Example 1 Use 105μm high-purity rolled copper foil with a copper content greater than 99.9%. Cut the copper foil into 100*120 mm sizes and go through the following steps: Step 1 Annealing: Place the cut copper foil in an oven at 280°C for 2 minutes, then air cool.

[0020] Step 2 Electrolytic degreasing: Place the copper foil annealed in step 1 in a 3.5wt% BASF degreasing agent at a temperature of 40°C and a current density of 15A / dm 2 , electroplating time 10s.

[0021] Step 3: First water washing: Soak the copper foil after electrolytic degreasing in step (2) in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0022] Step 4: Pickling: Soak the copper foil after the first water washing in step 3 in the pickling solution for 10 seconds. The purpose of pickling is to clean the oxide layer on the rough surface of the copper foil without affecting the uniformity of subsequent electroplating. The pickling solution temperature is 25°C, H + Concentration 120g / L, Cu + Concentration 30g / L.

[0023] Step 5: Second water washing: Soak the copper foil after pickling in step 4 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8ppm, and soak for 10 seconds.

[0024] Step 6: First roughening: Put the copper foil after the second water washing in step 5 into the roughening solution with a current density of 30A / dm 2 , electroplating time 8s, the temperature of the roughening bath is 40℃, Cu + Concentration 40g / L, H + Concentration 120g / L.

[0025] Step 7: Third water washing: Soak the copper foil after the first roughening in step 6 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0026] Step 8 First curing: Put the copper foil washed for the third time in step 7 into the curing solution. The temperature of the curing tank is 25°C. + Concentration 50g / L, H + Concentration 80g / L, current density 40A / dm 2 , electroplating time 10s. The purpose of curing is to grow the roughened copper nodules and strengthen the roughened structure.

[0027] Step 9: Fourth water washing: Soak the copper foil after the first curing in step 8 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0028] Step 10: Second roughening: Put the copper foil after the fourth water washing in step 9 into the roughening solution with a current density of 30A / dm 2 , electroplating time 8s, the temperature of the roughening bath is 40℃, Cu + Concentration 40g / L, H + Concentration 120g / L.

[0029] Step 11: Fifth water washing: Soak the copper foil roughened for the second time in step 10 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0030] Step 12 Second curing: Put the copper foil washed for the fifth time in step 11 into the curing solution. The temperature of the curing tank is 25°C. + Concentration 50g / L, H + Concentration 80g / L, current density 40A / dm 2 , electroplating time 10s.

[0031] Step 13 Sixth water washing: Soak the copper foil after the second curing in step 12 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0032] Step 14: Passivation: Place the copper foil after the sixth water washing in step 13 in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 15g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 8g / L, the sodium molybdate concentration is 6g / L, the ammonium citrate concentration is 15g / L, the sorbitol concentration is 3g / L, the sodium dodecyl sulfate concentration is 0.6g / L, the pH value is 10, and the current density is 3A / dm 2 , electroplating time 2min. The purpose of passivation is to improve the heat resistance and oxidation resistance of copper foil, so that it can be stored for a long time.

[0033] Step 15: Seventh water washing: Soak the copper foil after passivation in step 14 in water for 10 seconds, with a pH value of 7.2 and a chloride ion content of 0.8 ppm, for 10 seconds.

[0034] Step 16: Silane coating: Coat the copper foil washed for the seventh time in step 15 with silane. The temperature of the silane coupling agent is 25°C. Take 2 ml and roll evenly.

[0035] Step 17: Drying: Dry the copper foil coated with silane in step 16 at a temperature of 100° C. in an oven for 20 seconds to obtain a rolled copper foil.

[0036] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it can be immersed in tin solution at 288℃ for 23 minutes without cracking and baked at high temperature of 210℃ for 40 minutes without oxidation and discoloration.

[0037] Example 2 The preparation process is basically the same as that in Example 1, except that: Step 14: Passivation: The copper foil after the sixth water washing in step 13 is placed in a solution for passivation treatment. The temperature of the plating solution is 40°C, the concentration of zinc oxide is 12g / L, the concentration of sodium hydroxide is 90g / L, the concentration of nickel sulfate is 5g / L, the concentration of sodium molybdate is 3g / L, the concentration of ammonium citrate is 15g / L, the concentration of sorbitol is 3g / L, the concentration of sodium dodecyl sulfate is 0.6g / L, the pH value is 10, the current density is 3A / dm2, and the electroplating time is 2min.

[0038] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it was immersed in tin solution at 288℃ for 20min without cracking, and was oxidized and discolored after being baked at high temperature of 210℃ for 40min.

[0039] Example 3 The preparation process is basically the same as that in Example 1, except that: Step 14: Passivation: Place the copper foil after the sixth water washing in step 13 in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 8g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 8g / L, the sodium molybdate concentration is 6g / L, the ammonium citrate concentration is 15g / L, the sorbitol concentration is 3g / L, the sodium dodecyl sulfate concentration is 0.6g / L, the pH value is 10, and the current density is 3A / dm 2 , electroplating time 2min.

[0040] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it was immersed in tin liquid at 288℃ for 10 minutes and did not oxidize and discolor after being baked at high temperature of 210℃ for 40 minutes.

[0041] Example 4 The preparation process is basically the same as that in Example 1, except that: Step 14: Passivation: Place the copper foil after the sixth water washing in step 13 in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 15g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 8g / L, the sodium molybdate concentration is 6g / L, the ammonium citrate concentration is 10g / L, the sorbitol concentration is 5g / L, the sodium dodecyl sulfate concentration is 0.2g / L, the pH value is 9, and the current density is 3A / dm 2 , electroplating time 2min.

[0042] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it was immersed in tin liquid at 288℃ for 10 minutes and did not oxidize and discolor after being baked at high temperature of 210℃ for 40 minutes.

[0043] Example 5 The preparation process is basically the same as that in Example 1, except that: Step 14: Passivation: Place the copper foil after the sixth water washing in step 13 in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 8g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 5g / L, the sodium molybdate concentration is 3g / L, the ammonium citrate concentration is 15g / L, the sorbitol concentration is 1g / L, the sodium dodecyl sulfate concentration is 0.8g / L, the pH value is 12, and the current density is 3A / dm 2 , electroplating time 2min.

[0044] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it was immersed in tin liquid at 288℃ for 5 minutes to cause the board to explode, and was baked at high temperature of 210℃ for 40 minutes to cause oxidation and discoloration.

[0045] Example 6 The preparation process is basically the same as that in Example 1, except that: Step 2 Electrolytic degreasing: Place the copper foil annealed in step 1 in a 3wt% BASF degreasing agent at 25°C and a current density of 15A / dm 2 , electroplating time 10s.

[0046] Step 14: Passivation: Place the copper foil after the sixth water washing in step 13 in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 15g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 8g / L, the sodium molybdate concentration is 6g / L, the ammonium citrate concentration is 15g / L, the sorbitol concentration is 3g / L, the sodium dodecyl sulfate concentration is 0.6g / L, the pH value is 8, and the current density is 3A / dm 2 , electroplating time 2min.

[0047] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it was immersed in tin liquid at 288℃ for 5 minutes without being oxidized and discolored after being baked at high temperature of 210℃ for 40 minutes.

[0048] Comparative Example 1 The preparation process is basically the same as that in Example 1, except that: There is no step 14 passivation.

[0049] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it exploded when immersed in tin liquid at 288℃ for 5 minutes, and was oxidized and discolored when baked at high temperature of 210℃ for 40 minutes, with poor performance.

[0050] Comparative Example 2 The preparation process is basically the same as that in Example 1, except that: The copper foil after the sixth water washing in step 13 is placed in a solution for passivation treatment. The plating solution temperature is 40°C, the zinc oxide concentration is 18g / L, the sodium hydroxide concentration is 90g / L, the nickel sulfate concentration is 8g / L, the sodium molybdate concentration is 2g / L, the ammonium citrate concentration is 15g / L, the sorbitol concentration is 6g / L, the sodium dodecyl sulfate concentration is 1.6g / L, the pH value is 10, and the current density is 3A / dm 2 , electroplating time 2min.

[0051] Results: After the surface treatment of the 105μm rolled copper foil through the above process, it exploded when immersed in tin liquid at 288℃ for 12 minutes, and was oxidized and discolored when baked at high temperature of 210℃ for 40 minutes, and its performance was poor.

[0052] Example Immersion tin (288°C) Oxidation status after baking at 210℃ for 40min Example 1 Tin immersion 23min board burst, very good heat resistance Unoxidized Example 2 Tin immersion for 20 minutes, the board explodes, and the heat resistance is very good Unoxidized Example 3 Tin immersion for 15 minutes, the board explodes, and the heat resistance is very good Unoxidized Example 4 Tin immersion for 15 minutes, the board explodes, and the heat resistance is very good Unoxidized Example 5 Tin immersion for 20 minutes, the board explodes, and the heat resistance is very good Unoxidized Example 6 Tin immersion for 15 minutes, the board explodes, and the heat resistance is very good Unoxidized Comparative Example 1 Tinning for 5 minutes causes board explosion, poor heat resistance Oxidation Comparative Example 2 Tinning for 12 minutes causes the board to explode, and the heat resistance is poor Oxidation

[0053] Performance test results: It can be seen from Examples 1-6 and Comparative Examples 1-2 that the tinning time of Examples 1-6 is long, among which Example 1 has the best result. It can be seen that by optimizing the passivation step and electroplating the Zn-Ni-Mo alloy layer, the heat resistance of the rolled copper foil is greatly improved.

[0054] It can be seen from Examples 1-6 and Comparative Examples 1-2 that in Examples 1-6, there is no oxidation after baking at 210°C for 40 minutes. This shows that the passivation step is optimized and the electroplated Zn-Ni-Mo alloy layer has good oxidation resistance for the rolled copper foil.

[0055] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A passivation process in a surface treatment process of a rolled copper foil, characterized in that: The passivation process conditions are as follows: the temperature of the plating solution is 35-45°C, the concentration of zinc oxide is 8-15g / L, the concentration of sodium hydroxide is 80-100g / L, the concentration of nickel sulfate is 5-10g / L, the concentration of sodium molybdate is 3-8g / L, the concentration of ammonium citrate is 10-20g / L, the concentration of sorbitol is 1-5g / L, the concentration of sodium dodecyl sulfate is 0.2-1g / L, the pH value is 8-12, and the current density is 1-5A / dm 2 , electroplating time 1-3min.

2. The passivation process in the surface treatment process of rolled copper foil according to claim 1, characterized in that: The passivation process conditions are as follows: plating solution temperature 40°C, zinc oxide concentration 15g / L, sodium hydroxide concentration 90g / L, nickel sulfate concentration 8g / L, sodium molybdate concentration 6g / L, ammonium citrate concentration 15g / L, sorbitol concentration 3g / L, sodium dodecyl sulfate concentration 0.6g / L, pH value 10, current density 3A / dm 2 , electroplating time 2min.

3. A surface treatment process for rolled copper foil, using 105-140 μm high-purity rolled copper foil with a copper mass content greater than 99.9%, characterized in that: The specific steps are as follows: annealing, electrolytic degreasing, first water washing, pickling, second water washing, first roughening, third water washing, first curing, fourth water washing, second roughening, fifth water washing, second curing, sixth water washing, passivation as described in any one of claims 1-2, seventh water washing, silane coating, and drying.

4. The surface treatment process of rolled copper foil according to claim 3, characterized in that: The annealing conditions are: maintaining the temperature in an oven at 270-290° C. for 1-3 minutes, and then air cooling.

5. The surface treatment process of rolled copper foil according to claim 3, characterized in that: The electrolytic degreasing conditions are: BASF degreasing agent with a mass fraction of 3-4wt% or more, temperature of 25-50℃, current density of 10-20A / dm 2 , electroplating time 5-15s.

6. The surface treatment process of rolled copper foil according to claim 3, characterized in that: The process conditions of the first and second roughening are as follows: the temperature of the roughening bath is 25-50°C, Cu + Concentration 30-50g / L, H + Concentration 110-130g / L, current density 15-40A / dm 2 , electroplating time 5-10s.

7. The surface treatment process of rolled copper foil according to claim 3, characterized in that: The process conditions of the first and second curing are as follows: the temperature of the curing tank is 20-30°C, Cu + Concentration 40-60g / L, H + Concentration 70-90g / L, current density 30-50A / dm 2 , electroplating time 5-15s.

8. The process for surface treatment of rolled copper foil according to claim 3, characterized in that: The silane coating conditions are as follows: the temperature of the silane coupling agent is 20-30° C., and 1-3 ml is taken and rolled evenly.

9. The surface treatment process of rolled copper foil according to claim 3, characterized in that: The pickling conditions are as follows: pickling solution temperature 20-30°C, H + Concentration 110-130g / L, Cu + Concentration 20-40g / L, soak for 5-15s.

10. The process for surface treatment of rolled copper foil according to claim 3, characterized in that: The water washing conditions are as follows: pH value is 7-7.5, chloride ion content is 0.6-1ppm, and soaking is 5-15s.

11. A rolled copper foil, characterized in that: The method is prepared by the surface treatment process as described in claims 3-10.

Citation Information

Cited By

  • Rolled copper foil anti-oxidation treatment fluid, surface treatment fluid and surface treatment method

    CN121087587A